Enteric Duplication Cyst Containing Squamous and Respiratory Epithelium: An Interesting Case of a Typically Pediatric Entity Presenting in an Adult Patient - Jessica Leigh Baumann; Charmi Patel (Case Reports in Gastrointestinal Medicine)
Enteric duplication cysts are rare congenital malformations that can occur at any point along the digestive tract, most commonly the small bowel. They are characterized by the presence of an outer layer of smooth muscle and an inner lining of mucosa that may resemble any portion of the digestive tract. Less commonly, cases have been reported that also contain mucosal components of nonintestinal origin. This entity is typically diagnosed in young children, but occasionally presents in adolescence and young adulthood. We present a rare case of a 21-year-old male who presented with nonspecific symptoms of abdominal discomfort and weight loss and was later found to have a 9 cm nonenhancing mass in the distal ileum on CT imaging. Laparoscopic dissection of the mass revealed a cystic lesion lined mainly by pseudostratified ciliated columnar respiratory-type epithelium, with patchy areas of squamous epithelium as well as villous columnar epithelium resembling small bowel. The unique histology and advanced patient age make this case a unique presentation of what is already a rare pathological entity.